The Restricted Detour Polynomial of the Theta Graph (AL-Rafidain Journal of Computer Sciences and Mathematics, 2020)
= P. The main goal of this paper is to obtain the restricted detour polynomial of the theta graph. Moreover, the restricted detour index of the theta graph will also be obtained.]]>
Keywords: Restricted detour distance; restricted detour polynomial; Theta graphs